Analysis of the Need for Technology Integration and Development of Four Cs Skills in Science Learning in Elementary Schools in Pinrang Regency - Saleha Saleha; Masnur Masnur; Nadar Nadar; Elihami Elihami (Edumaspul: Jurnal Pendidikan, 2024)
This study investigates technology integration and Four Cs skills development (Critical Thinking, Creativity, Collaboration, Communication) in elementary school science learning in Pinrang Regency, South Sulawesi. Using a mixed-methods sequential explanatory design, the research involved 120 science teachers and 360 students from grades IV-VI across 30 elementary schools. Data were collected through structured questionnaires, in-depth interviews, and classroom observations, then analyzed using descriptive statistics, Structural Equation Modeling (SEM), and thematic analysis. The findings reveal a significant gap between awareness and implementation of technology integration. While 82% of teachers recognized the importance of technology in learning, only 34% felt digitally competent (mean = 3.04). Four Cs skills implementation showed moderate achievement with collaboration scoring highest (3.35), followed by critical thinking (3.18), communication (3.07), and creativity lowest (2.94). SEM analysis confirmed that teachers' digital competencies significantly predict Four Cs implementation (β = 0.647, p < 0.001), with infrastructure acting as a moderator (β = 0.234, p < 0.05). The model explained 67.8% of variance in Four Cs implementation. Key barriers included technological infrastructure (89.2%), digital competencies (75.8%), institutional support (66.7%), time constraints (53.3%), and resistance to change (45.0%). Significant disparities exist between urban schools (25 Mbps bandwidth) and rural schools (8 Mbps). The developed Layered Technology Integration model demonstrated high validity (CVR = 0.89) and effectiveness in pilot implementation. The study recommends systematic professional development programs, infrastructure improvement, and the development of Project-based Learning models integrated with TPACK framework to enhance 21st century skills in elementary science education.